Point-of-Care, Peer-Comparator Colonoscopy Practice Audit: The Canadian Association of Gastroenterology Quality Program – Endoscopy. (2011) - Armstrong, David; Hollingworth, Roger; MacIntosh, Donald; Chen, Ying; Daniels, Sandra; Gittens, Stuart; Bridges, Ron; Sinclair, Paul; Dubé, Catherine
Abstract : BACKGROUND: Point-of-care practice audits allow documentation of procedural outcomes to support quality improvement in endoscopic practice. OBJECTIVE: To evaluate a colonoscopists' practice audit tool that provides point-of-care data collection and peer-comparator feedback. METHODS: A prospective, observational colonoscopy practice audit was conducted in academic and community endoscopy units for unselected patients undergoing colonoscopy. Anonymized colonoscopist, patient and practice data were collected using touchscreen smart-phones with automated data upload for data analysis and review by participants. The main outcome measures were the following colonoscopy quality indicators: colonoscope insertion and withdrawal times, bowel preparation quality, sedation, immediate complications and polypectomy, and biopsy rates. RESULTS: Over a span of 16 months, 62 endoscopists reported on 1279 colonoscopy procedures. The mean cecal intubation rate was 94.9% (10th centile 84.2%). The mean withdrawal time was 8.8 min and, for nonpolypectomy colonoscopies, 41.9% of colonoscopists reported a mean withdrawal time of less than 6 min. Polypectomy was performed in 37% of colonoscopies. Independent predictors of polypectomy included the following: endoscopy unit type, patient age, interval since previous colonoscopy, bowel preparation quality, stable inflammatory bowel disease, previous colon polyps and withdrawal time. Withdrawal times of less than 6 min were associated with lower polyp removal rates (mean difference −11.3% [95% CI −2.8% to −19.9%]; P=0.01). DISCUSSION: Cecal intubation rates exceeded 90% and polypectomy rates exceeded 30%, but withdrawal times were frequently shorter than recommended. There are marked practice variations consistent with previous observations. CONCLUSION: Real-time, point-of-care practice audits with prompt, confidential access to outcome data provide a basis for targeted educational programs to improve quality in colonoscopy practice.